Guinness World Records, 2023 - Glenday, Craig ([London, England] : Guinness World Records Limited, 2022)
Presents the biggest, smallest, fastest, longest, and other record setters for 2022 in the categories of space, Earth, animals, humans, fantastic feats, science and technology, arts and media, and sports.
Space -- Life on Earth -- Humans -- Human body -- Extraordinary exploits -- Around the world in 300 records -- Epic engineering -- Entertainment -- Modern world -- Sports.
Includes index.
Young Adult
Keywords: Curiosities and wonders; World records; Trivia and miscellanea; Illustrated works